2022
DOI: 10.3390/agronomy12020506
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of the Effects of Plastic Mulch Films on Soil Nutrient, Yields and Soil Microbiome in Three Vegetable Fields

Abstract: Plastic film mulching is a common practice to increase vegetable yields. However, the effects of plastic mulch films on different vegetable fields remain largely unknown. In the current study, biodegradable mulch films (BDMs) and polyethylene mulch films (PEMs) were used to explore their effects on three vegetable fields (broccoli, chili pepper and garlic). Compared with bare soil, both BDMs and PEMs could effectively maintain higher exchangeable potassium contents in rhizosphere soil, and significantly increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 56 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…China [186] Water spinach (I. aquatica). Production of water spinach was significantly improved with rice straw mulching.…”
Section: Crop Rotationmentioning
confidence: 99%
“…China [186] Water spinach (I. aquatica). Production of water spinach was significantly improved with rice straw mulching.…”
Section: Crop Rotationmentioning
confidence: 99%
“…It can be hypothesized that arbuscular mycorrhizal fungi (AMF) may also be indirectly affected due to the effects of MPs on soil properties like bulk density, pore structure, water retention, and soil aggregation that condition AMF (Leifheit et al., 2021). Indeed, some plastic mulches indirectly impact fungal and bacterial communities by increasing or decreasing those microorganisms’ abundance through the availability of nutrient (e.g., exchangeable potassium and nitrate; Frey et al., 2008; Koitabashi et al., 2012; Muñoz et al., 2017; Shan et al., 2022).…”
Section: Effects Of Mps On Soil Biotamentioning
confidence: 99%
“…Indeed, some plastic mulches indirectly impact fungal and bacterial communities by increasing or decreasing those microorganisms' abundance through the availability of nutrient (e.g., exchangeable potassium and nitrate; Frey et al, 2008;Koitabashi et al, 2012;Muñoz et al, 2017;Shan et al, 2022).…”
Section: Fungimentioning
confidence: 99%
“…Recent findings have shown that organic mulch helps regulate soil-microbial communities in tea and litchi [15,16]. In addition, plastic mulch films (biodegradable mulch and polyethylene mulch) can increase microbial abundances in the rhizosphere [17].…”
Section: Introductionmentioning
confidence: 99%